MENINGKATKAN LITERASI KEUANGAN DAN INVESTASI DIGITAL KALANGAN PEMILIK UMKM DI KABUPATEN SUKOHARJO - Prastiwi, Septi Kurnia; Astuti, Yuni; Ardiansyah, Mufti Arief; Nurohman, Yulfan Arif; Yahya, Alvin; Mahirta, Irna; Budiharto, Muhammad Akbar Dwi; Anjelisa, Ayun (ABDI MAKARTI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, yet they often face challenges related to financial literacy and limited access to sustainable financial strategies. This community service program aims to improve digital investment literacy and strengthen investment intentions among MSME owners through a structured training and mentoring approach. The program involved MSMEs under the auspices of BMT Mazaya and was implemented using a participatory empowerment method that integrated educational sessions, interactive discussions, practical simulations, and behavioral reinforcement based on the Theory of Planned Behavior. The results showed that the program effectively improved participants' understanding of digital investment concepts and increased their interest in engaging in formal financial instruments. This intervention also contributed to strengthening participants' attitudes, perceived behavioral control, and subjective norms toward investment activities. Specifically, participants demonstrated greater awareness and confidence in exploring stock investment opportunities on the Indonesia Stock Exchange. Furthermore, the integration of mentoring as a follow-up strategy played a key role in bridging the gap between financial knowledge and actual behavioral intentions. These findings highlight that literacy programs combined with ongoing support are more effective in promoting sustainable financial behavior among MSMEs. Overall, this program contributes to improving financial resilience and supporting the long-term sustainability of MSMEs by increasing investment literacy